2020
DOI: 10.1080/0092623x.2020.1810185
|View full text |Cite
|
Sign up to set email alerts
|

Romantic Relationship Conflict Due to the COVID-19 Pandemic and Changes in Intimate and Sexual Behaviors in a Nationally Representative Sample of American Adults

Abstract: In early 2020, the novel coronavirus 2019 (COVID-19) spread across the United States and mitigation measures drastically affected the daily lives of Americans. In this study, we assessed the association between COVIDrelated relationship conflict and changes in intimate and sexual behaviors and experiences. Using data from an online nationally representative probability survey of 1,010 American adults in April 2020, we estimated the impact of coronavirus-related relationship conflict on changes in intimate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
245
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(296 citation statements)
references
References 62 publications
12
245
2
9
Order By: Relevance
“…However, few studies investigated whether these negative feelings affect sexuality during a pandemic. In line with our results, Panzeri et al (17) showed that the negative aspects of lockdown can affect the quality of sexual life, while Luetke et al (18) showed that Americans experienced more conflict in their romantic partnerships, owing to changes in their intimate and sexual lives. Sexual health is an important parameter for well-being because it impacts our psychological and emotional state.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, few studies investigated whether these negative feelings affect sexuality during a pandemic. In line with our results, Panzeri et al (17) showed that the negative aspects of lockdown can affect the quality of sexual life, while Luetke et al (18) showed that Americans experienced more conflict in their romantic partnerships, owing to changes in their intimate and sexual lives. Sexual health is an important parameter for well-being because it impacts our psychological and emotional state.…”
Section: Discussionsupporting
confidence: 91%
“…Since the disease originated in China, Asia-phobic reactions have been reported at the beginning of the epidemic, in various regions of the world (18). Our results revealed that Italian people tend to engage in avoidant behavior toward people with pneumonia-like symptoms rather than toward Asians.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Drawing on existing relationship models, scholars have suggested the stresses of the COVID-19 pandemic will likely threaten romantic relationships (Pietromonaco and Overall 2020). Documented relationship consequences of COVID-19 include increased relationship conflict (Luetke et al 2020), reduced sexual frequency (Lehmiller et al 2020), and high rates of contacting alternative sexual and romantic partners (Lehmiller et al 2020). COVID-19 has also created uncertainty in income, employment, or housing stability, which may threaten single men and women's ability to meet the economic prerequisites to marriage and delay transitions into marriage (Oppenheimer 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This surprising association could be explained by the fact that youth living with two parents may have been more exposed to marital conflict, a significant stressor for adolescents that can generate anxiety [82]. Indeed, a study conducted among American adults shows that they have experienced conflict escalations in their romantic partnerships [53]. This explanation appears plausible since the study took place at the beginning of confinement.…”
Section: Sociodemographic Characteristics and Internalized Symptomsmentioning
confidence: 99%